Social Network Analysis: A Case Study in Turkey - Varol, Asaf; Aydin, Ozgur (Acad Conferences Ltd, 2010)
In the last decade, some online social networks such as YouTube, Facebook, Twitter, Linkedln and Jhoos have been accessed by a large number of internet users. Because of these networks, most users spend their spare time surfing the internet. Although social networks provide a number of benefits in terms of developing and sharing knowledge, there are some disadvantages that can make a person's life really miserable on occasion. Within the last few years in Turkey, some secret videos and voice recordings have been broadcast on these social networks without the permission of the people involved. Therefore, some people commit suicide because of the public revelation of their private lives. More than a year ago, some people were arrested and put into jail because they had been broadcasting private recordings on social network sites. Social networks can be used as free advertising environments; even these pages can be used as a place where links can be posted to pornographic websites. Terrorist groups can use social networks not only as tools for propaganda, but also as a communication environment with their members. Because of Turkey's anti-propaganda campaign and Mustafa Kemal Ataturk, who is the founder of the Turkish Republic, access to YouTube in Turkey has been forbidden. In this study, a survey was conducted using a number of people in Turkey via the internet in order to measure and evaluate the role of social networks on human behavior. There were more than 20 statements presented to the social network users, where the number of respondents was just over 1000. They were also asked to comment on the social network situation. The survey was evaluated using SPSS software. The relationship between age, gender, income level, the person's social life etc. was investigated and critiqued. The advantages and disadvantages of social networks were discussed. At the end of this paper, some recommendations will be given.
7th International Conference on Intellectual Capital, Knowledge Management and Organisational Learning -- NOV 11-12, 2010 -- Hong Kong Polytechn Univ, Hong Kong, PEOPLES R CHINA
Keywords: social networking; YouTube; Facebook; Linkedln; Jhoos